Prevalence, risk factors, and management of ascites in the western sub-divisional hospitals of Fiji: a multi-center retrospective study - Bancod, Robert A.; Gogoi, Abhijit; Buenafe, Dennis G. (International Surgery Journal, 2024)
Background: Ascites, a condition characterized by fluid accumulation in the abdominal cavity, is a common complication of chronic liver disease and other serious health conditions. In resource-limited settings such as Fiji, managing ascites presents unique challenges. This study investigates the prevalence, associated risk factors, and current management approaches for ascites in the Western Sub-Divisional Hospitals of Fiji, focusing on population demographics and healthcare practices. Methods: This retrospective study analyzed patient records from January 2021 to December 2023 across five hospitals—Sigatoka, Nadi, Ba, Tavua and Rakiraki. Data on demographics, medical history, lifestyle factors and treatment practices were collected. The study adhered to ethical standards, with approval from the Fiji National Research. Results: Ascites primarily affected individuals over the age of 50, with a higher prevalence among men and individuals of Indian descent. Key risk factors included alcohol abuse, chronic liver disease, and metabolic syndrome. Management typically involved sodium restriction, diuretics and in limited cases, Transjugular Intrahepatic Portosystemic Shunt (TIPSS) due to accessibility constraints. Conclusions: The findings highlight a need for culturally responsive healthcare strategies, improved screening, and multidisciplinary treatment protocols to manage and prevent ascites effectively in this population. Enhanced public health initiatives and clinical guidelines could significantly impact patient outcomes in Fiji.